Closed-loop interaction with the cerebral cortex using a novel micro-ECoG-based implant: the impact of beta vs. gamma stimulation frequencies on cortico-cortical spectral responses*. Issue 4 (2nd October 2017) - Gkogkidis, C. Alexis; Wang, Xi; Schubert, Tobias; Gierthmühlen, Mortimer; Kohler, Fabian; Schulze-Bonhage, Andreas; Burgard, Wolfram; Rickert, Jörn; Haberstroh, Jörg; Schüttler, Martin; Stieglitz, Thomas; Ball, Tonio
Abstract: Medical brain implants for closed-loop interaction with the cerebral cortex promise new treatment options for brain disorders, and thus great efforts are being made to develop devices for long-term application. Closed-loop interaction can be implemented using electrophysiological recording techniques, and can be used to modulate local cortical activity or long-range functional connectivity. In a case study performed in sheep chronically implanted with a novel micro-electrocorticography-based device, we show that (1) open-loop single-pulse electrical stimulation (SPES) elicited the well-known cortico-cortical evoked potentials (CCEPs), and (2) closed-loop repetitive-pulse electrical stimulation (RPES) elicited specific cortico-cortical spectral responses (CCSRs). CCSRs were spatially focalized in the gamma band, compared with beta band independent of RPES frequency. The topography of CCSRs was different compared with CCEPs, suggesting that CCEPs and CCSRs capture different aspects of cortico-cortical connectivity. We propose that CCSRs provide new useful measures of functional connectivity, and that in particular gamma-band CCSRs may be an optimal choice if spatially precise closed-loop interaction is desired. However, the parameter space of micro-electrocorticography stimulation patterns and associated changes in μECoG frequency bands needs to be further explored and many questions remain before closed-loop brain implants can be used in clinical applications.